Active postlarval forms of plume-footed Eatoniana (Trombidiformes: Parasitengona, Erythraeidae) in the Eocene Baltic amber - Sidorchuk, Ekaterina A.; Konikiewicz, Marta; Welbourn, W. Calvin; Mąkol, Joanna (Zootaxa, 2019)
The discovery of active postlarval forms (deutonymph and adult) of erythraeid Eatoniana in Eocene Baltic amber is associated with the first description of named fossil species assigned to that genus. Species of Eatoniana, having the plume-like setae on terminal segments of leg IV, reveal the high consistency of characters, confirmed both for extinct and extant members of the genus. The main difference between Eatoniana crinita sp. nov. and other “plume-footed” congeners is the shape of modified setae arising at genu and tibia IV.